Epilepsy diagnosis and management of children in Kenya: review of current literature - Samia, P; Hassell, J; Hudson, J; Murithi, M; Kariuki, S; Newton, C; Wilmshurst, J (Dove Medical Press, 2019)
Introduction: The growing impact of non-communicable diseases in low- to middle-income countries makes epilepsy a key research priority. We evaluated peer-reviewed published literature on childhood epilepsy specific to Kenya to identify knowledge gaps and inform future priorities. Methodology: A literature search utilizing the terms "epilepsy" OR "seizure" as exploded subject headings AND "Kenya" was conducted. Relevant databases were searched, generating 908 articles. After initial screening to remove duplications, irrelevant articles, and publications older than 15 years, 154 papers remained for full-article review, which identified 35 publications containing relevant information. Data were extracted from these reports on epidemiology, etiology, clinical features, management, and outcomes. Results: The estimated prevalence of lifetime epilepsy in children was 21-41 per 1,000, while the incidence of active convulsive epilepsy was 39-187 cases per 100,000 children per year. The incidence of acute seizures was 312-879 per 100,000 children per year and neonatal seizures 3,950 per 100,000 live births per year. Common risk factors for both epilepsy and acute seizures included adverse perinatal events, meningitis, malaria, febrile seizures, and family history of epilepsy. Electroencephalography abnormalities were documented in 20%-41% and neurocognitive comorbidities in more than half. Mortality in children admitted with acute seizures was 3%-6%, and neurological sequelae were identified in 31% following convulsive status epilepticus. Only 7%-29% children with epilepsy were on antiseizure medication. Conclusion: Active convulsive epilepsy is a common condition among Kenyan children, remains largely untreated, and leads to extremely poor outcomes. The high proportion of epilepsy attributable to preventable causes, in particular neonatal morbidity, contributes significantly to the lifetime burden of the condition. This review reaffirms the ongoing need for better public awareness of epilepsy as a treatable disease and for national-level action that targets both prevention and management.